TAKĀFUL IN NIGERIA. (2013)
Takāful, Islamic mutual cooperative insurance, is fast gaining grounds all over the world and many countries have tapped into its potentials to grow their economies. Nigeria also licensed Takāful windows to three conventional insurance outfits (African Alliance PLC, Niger Insurance PLC and Cornerstone Insurance PLC). Studies have addressed banking and other aspects of Islamic finance in Nigeria but none has examined the practice of Takāful. This study, therefore, investigates the extent and form of practice, level of awareness of operations and patronage of Takāful in Nigeria with a view to determining the challenges and prospects of its full operation. The study adopted Pascal and Fermat’s theory of probability which determines actuarial calculations and risk assessment in insurance business. Survey design involving the use of random and purposive sampling methods was adopted in the administration of copies of a questionnaire to 270 Civil Servants, 102 Engineers, 105 Accountants, 100 Bankers, 210 Teachers, 80 Lawyers and 33 Artisans in six randomly selected states (Kano, Gombe, Kwara, Edo, Imo and Ogun) in Nigeria’s geo-political regions and purposively selected Lagos and Abuja, for their economic and political importance respectively. In-depth interviews were conducted with nine top Takāful officials of the windows. Qualitative data were subjected to content analysis, qualitative data were analysed using percentages. Takāful practice in Nigeria remained at the windows level. The windows offered both general and life Takāful products. They adopted Al-Muḍārabah (Profit-and-loss sharing) model and operated the account components required of Takāful operation (Participants’ Account and Participants’ Special Account) in line with standard international practice. The windows did not disclose the volume of subscription but confirmed low patronage. They were found not to have done enough in awareness creation, hence, the low patronage could be consequent on public’s poor knowledge of the workings of Takāful. Takāful officials identified lack of support institutions like Central Sharī ‘ah Council, liquid secondary market, re-takāful outfits and few Sharī ‘ah-compliant investment products as challenges to confront full Takāful operations. They mentioned the need for personnel, education and awareness creation as germane. Meanwhile, 69.8% of respondents were aware of the existence of the windows, but very few (26.5%) subscribed to Takāful products. About half of these were satisfied with their subscriptions. Moreover, 65.2% of respondents were willing to subscribe to Takāful plans. A large percentage of respondents UNIVERSITY OF IBADAN LIBRARY xix (83.6%) opined that full Takāful operation would succeed in Nigeria. Furthermore, respondents believed that the following could serve as prospects for Takāful: the Muslim population (70.3%), existence of many Islamic organisations (76.0%), poverty level in Nigeria (71.5%) and the existence of ḥalāl (lawful) investment products in Nigeria (68.8%). In addition, 57.7% of respondents supported the need for appropriate regulations for Takāful. Takāful in Nigeria, though still at the windows level, is consistent with acceptable global practice. Awareness and patronage are still low but there is a great potential for the country to benefit maximally from this system. Thus, government needs to create awareness, build institutions and provide regulations for its full take off.